Role of DJ-1 in Immune and Inflammatory Diseases - Zhang, Lulu; Wang, Jincheng; Wang, Jiajia; Yang, Bo; He, Qiaojun; Weng, Qinjie (Frontiers in Immunology, 2020)
The DJ-1 protein, known as an oxidative stress sensor, participates in the onset of oxidative stress-related diseases such as cancer, neurodegenerative disorders, type 2 diabetes, and male infertility. Although DJ-1 has been extensively studied for more than two decades, evidence has only recently emerged that it plays a key role in immune and inflammatory disorders. The immune regulatory function of DJ-1 is achieved by modulating the activation of several immune cells including macrophages, mast cells, and T cells via reactive oxygen species (ROS)-dependent and/or ROS-independent mechanisms. This review describes the current knowledge on DJ-1, focusing on its immune and inflammatory regulatory roles, and highlights the significance of DJ-1 as a novel therapeutic target for immune and inflammatory diseases.